Musik dan Pergeseran Kesadaran - Ovan Bagus (PANGGUNG, 2025)
This study discusses the presence of immanent consciousness through music. The issue discussed is how this immanent reality is present in the practice of playing music. Thus, the locus of this research is a study of the aesthetic experience of musicians when playing music. This is because, so far, when informants talk about the topic of music performance, the object of study tends to focus on practical matters such as the effectiveness of playing techniques, repertoire selection strategies, music analysis, and performance management. In Indonesia, music studies that discuss immanent experiences tend to emphasize non-sensory experiences: immanence as a type of transcendent experience that is divine, cosmic, or metaphysical. Conversely, the role of music in relation to the emergence of immanent experiences has not been widely discussed. Using Deleuze's concept of the virtual, this study elaborates on various immanent experiences in the context of traditional musicians. Research data was collected through interviews with two traditional musicians: Iwan Gunawan (drummer) and Maspon (saluang player). The data was then categorized into three types of experiences: empirical experiences, threshold experiences, and various sensations felt. Findings indicate that musical practice facilitates a shift in consciousness, moving from empirical perception toward immanent awareness. This shift enables musicians to encounter new forms of reality beyond standardized performance norms—emerging as pre-predicative modes of understanding.